2020
DOI: 10.1111/1744-7917.12772
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase C gamma (PLCγ) regulates soluble trehalase in the 20E‐induced fecundity of Apolygus lucorum

Abstract: Apolygus lucorum is the dominant pathogenic insect attacking Bacillus thuringiensis (Bt) cotton in China. Additionally, 20-hydroxyecdysone (20E) has important functions in many biological processes, including insect reproduction. Phospholipase C (PLC), which is an essential enzyme for phosphoinositide metabolism, is involved in 20E signal transduction, but its function in 20E-mediated reproduction in A. lucorum remains unclear. In this study, 20E increased AlPLCγ transcription as well as the abundance and acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
(59 reference statements)
0
8
0
Order By: Relevance
“…Meanwhile, cathepsin L1, protein takeout (hemolymph juvenile hormone binding protein), ATP-dependent RNA helicase p62-like, and myosin-9 isoform X1 were all down-regulated. Pairwise comparisons of the 20E/control group with U73122/control and 20E+U73122/control groups, respectively, revealed 20 and 18 DEPs, indicating that the panels of proteins regulated by 20E and PLC were significantly different, in agreement with the nature of these two reagents evoking distinct cellular responses (Liu et al , 2014; Chen et al , 2019; Tan et al , 2020).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Meanwhile, cathepsin L1, protein takeout (hemolymph juvenile hormone binding protein), ATP-dependent RNA helicase p62-like, and myosin-9 isoform X1 were all down-regulated. Pairwise comparisons of the 20E/control group with U73122/control and 20E+U73122/control groups, respectively, revealed 20 and 18 DEPs, indicating that the panels of proteins regulated by 20E and PLC were significantly different, in agreement with the nature of these two reagents evoking distinct cellular responses (Liu et al , 2014; Chen et al , 2019; Tan et al , 2020).…”
Section: Discussionmentioning
confidence: 82%
“…Through PLC/Ca 2+ signaling, 20E induces EcRE’s transcriptional activity by modulating PKC phosphorylation at Ser 21, which is important for its interaction with EcRE (Liu et al ,2014; Jing et al , 2015). In a previous study, we found 20E regulates AlTre-1 through AlPLCγ and alters Vg expression and ovary development, thereby facilitating female reproduction in A. lucorum (Tan et al , 2020). These data indicated that PLC participates in 20E signal transduction in a non-genomic pathway.…”
Section: Introductionmentioning
confidence: 82%
“…In Apolygus lucorum, downregulation of TRE leads to reduced ovary and ovariole size, decreased offspring numbers, and lower egg hatching rates. 28 In S. frugiperda, the inhibition of trehalase resulted in a shorter oviposition period for adults along with a slower development of ovaries, ultimately leading to reduced egg production. 29 These results demonstrate that TREs play important roles in the development and reproduction of holometabolous and paurometabolous insects, and are therefore strong candidate target genes for pest control.…”
Section: Introductionmentioning
confidence: 99%
“…The effective suppression of A. lucorum and other bugs population in cotton and other crops has been remained challenging mainly due to the high-mobility and host-plants transferring behaviors which occurs locally and seasonally among various crops. Studies have shown that these behaviors predominantly depend on interactions between the host plant volatiles and their highly-sensitive olfactory system [43][44][45][46]. However, a comprehensive and practical prospective deciphering this complex interaction in molecular level is still lacking.…”
Section: Introductionmentioning
confidence: 99%